Transhumanizm w kontekście odniesienia człowieka do rzeczy = Transhumanism in the perspective of the relations between humans and objects - Pawłowa, Elena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article analyses transhumanism as the anthropological strategy for the constitution of the objective human world. It presents also the historical forms of the relations between humans and objects, in which the objects are understood as the "sub-handed", "contr-handed", "proto-existing" or as an entertainment media. The subject, who had lost the attribute of "the hard-core" of the modernity, in the form presented by transhumanism becomes "the soft-ware human being" and it integrates systematically with its own artefacts. This point of view allows not only to overcome the absolutization of the antitheticality of the subject and object, but also to formulate the claims with regard to the borders between male and female, old and young, life and dead.
Keywords: transhumanizm; człowiek; rzecz; przedmiot; transhumanism; human being; thing; object